"Money makes the rooms go round": effects of affluence on room size and functions in 1890s houses - Humphris, Adrian; Mew, Geoff (Architectural History Aotearoa, 2023)
The 1890s was a decade in which a number of very large houses were either built or added to throughout the country. Their owners were commonly wealthy landowners or skilled businessmen. Room numbers and functions reflected the Victorian lifestyles of such people and tended to reflect similar trends in England although on a somewhat lesser scale. Room numbers of between 20 and 50 contrasted sharply with the four to eight rooms in an average family home of the time. In the latter the rooms were largely functional with the main family life centred around the kitchen and bedrooms. The big houses by contrast had extra rooms such as servants' quarters, ballrooms, billiard rooms, libraries, and dressing rooms and were often designed for entertaining and catering for visiting parties. The economic problems of the late 1880s and early '90s seem to have had little effect on those who might have been regarded as being on "The Rich List" whereas those on low incomes would not have been able to add more rooms such as parlours and bathrooms which became more common as conditions improved.